Coherently refreshing hypersonic phonons for light storage - Stiller, Birgit; Merklein, Moritz; Wolff, Christian; Vu, Khu; Ma, Pan; Madden, Steve J.; Eggleton, Benjamin J. (Optica, 2020)
Acoustic waves can serve as memory for optical information; however, propagating acoustic phonons in the gigahertz (GHz) regime decay on the nanosecond time scale. Usually this is dominated by intrinsic acoustic loss due to inelastic scattering of the acoustic waves and thermal phonons. Here we show a way to counteract the intrinsic acoustic decay of the phonons in a waveguide by resonantly reinforcing the acoustic wave via synchronized optical pulses. We experimentally demonstrate coherent on-chip storage in amplitude and phase up to 40 ns, 4 times the intrinsic acoustic lifetime in the waveguide. Through theoretical considerations, we anticipate that this concept allows for storage times up to microseconds within realistic experimental limitations while maintaining a GHz bandwidth of the optical signal.
CRIS-Team Scopus Importer:2021-06-29